2016
DOI: 10.1182/blood-2016-05-719757
|View full text |Cite
|
Sign up to set email alerts
|

C1q and HMGB1 reciprocally regulate human macrophage polarization

Abstract: Key Points C1q can form a multimolecular signaling complex with HMGB1, RAGE, and LAIR-1 in lipid rafts. C1q and HMGB1 together promote monocytes to differentiate to an anti-inflammatory phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
122
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 61 publications
(69 reference statements)
3
122
0
1
Order By: Relevance
“…Unlike the immediate signal for enhanced phagocytosis which is mediated by the collagen-like tails of C1q, and conserved with MBL, programmed efferocytosis required the full-length C1q molecule and was not shared with MBL. While primary human macrophages failed to upregulate Mer expression following prolonged stimulation with C1q alone (Hulsebus et al, 2016), human monocytes and dendritic cells cultured with the combination of C1q and HMGB1 upregulated Mer, suggesting with a conserved pathway in mouse and human cells (Son et al, 2016). These data are consistent with the observation that there is a reduction in the expression of pro-engulfment genes in macrophages from patients with SLE (Majai et al, 2014).…”
Section: Classical Functions: Complement Phagocytosis and Cytokinmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the immediate signal for enhanced phagocytosis which is mediated by the collagen-like tails of C1q, and conserved with MBL, programmed efferocytosis required the full-length C1q molecule and was not shared with MBL. While primary human macrophages failed to upregulate Mer expression following prolonged stimulation with C1q alone (Hulsebus et al, 2016), human monocytes and dendritic cells cultured with the combination of C1q and HMGB1 upregulated Mer, suggesting with a conserved pathway in mouse and human cells (Son et al, 2016). These data are consistent with the observation that there is a reduction in the expression of pro-engulfment genes in macrophages from patients with SLE (Majai et al, 2014).…”
Section: Classical Functions: Complement Phagocytosis and Cytokinmentioning
confidence: 99%
“…LAIR-1 engagement by C1q inhibits DC differentiation and activation either during steady state or inflammation and is suggested to help maintain monocyte tolerance (Son et al, 2012; Son and Diamond, 2015). In addition, C1q was reported recently to suppress the HMGB1-polarization of monocytes and maintain an anti-inflammatory M2-like macrophage, a pathway mediated through a complex with both RAGE and LAIR-1 and depending on the relative levels of C1q and HMGB1 (Son et al, 2016). …”
Section: Interaction With Cell Surface Proteins: Old and New Recepmentioning
confidence: 99%
“…A previous study demonstrated that C1q inhibits the proin ammatory effects of HMGB1 on monocytes 45 .…”
Section: Resultsmentioning
confidence: 97%
“…The proinflammatory activity of HMGB1 is well studied. However, the anti-inflammatory activity of HMGB1 also has been documented in multiple studies (49)(50)(51). Recently, it was shown that HMGB1 binds soluble CD52 and this complex binds with Siglec-10 on T-cells leading to SHP-1 (phosphatase) recruitment that dephosphorylates LCK and Zap70, thus activating an anti-inflammatory cascade (26,52).…”
Section: Discussionmentioning
confidence: 97%